Accelerometer-measured physical activity, sedentary behavior, and incidence of macrovascular and microvascular events in individuals with type 2 diabetes mellitus and prediabetes - Yannis Yan Liang; Yu He; Piao Huang; Hongliang Feng; Haiteng Li; Sizhi Ai; Jing Du; Huachen Xue; Yaping Liu; Jun Zhang; Lu Qi; Jihui Zhang (Journal of Sport and Health Science)
Background: Physical activity (PA) is considered beneficial for lowering cardiovascular risks following type 2 diabetes mellitus (T2DM) and prediabetes, but existing evidence relies mainly on self-reported measurements. We aimed to describe the intensity-specific dose–response associations of PA and sedentary behavior (SB) with macrovascular and microvascular events among individuals with T2DM and prediabetes. Methods: This study included 11,474 individuals with T2DM and prediabetes from the UK Biobank. PA, including total PA, moderate-to-vigorous intensity PA (MVPA), light-intensity PA (LPA), and SB, were measured by accelerometers over 7 days. MVPA was categorized according to the American Diabetes Association guideline-recommended level (at least 150 min/week), and total PA, LPA, and SB were grouped by tertiles. The outcomes were incidences of macrovascular events, microvascular events, heart failure (HF), and their combination (composite events). The events were ascertained using the International Classification of Diseases-10 (ICD-10) codes on the hospital or death records. Results: During a median follow-up of 6.8 years, 1680 cases were documented, including 969 macrovascular events, 839 microvascular events, and 284 incidents of HF. Accelerometer-measured PA, irrespective of intensity, was inversely associated with the risk of composite events and each outcome in the dose–response patterns. Regarding categorized PA, engagement in total PA (high vs. low) was associated with decreased risk of macrovascular events (hazard ratio (HR) = 0.80; 95% confidence interval (95%CI): 0.67–0.95), microvascular events (HR = 0.76; 95%CI: 0.63–0.93), and HF (HR = 0.46; 95%CI: 0.32–0.66). Adherence to MVPA, but not LPA, above the guideline-recommended level (at least 150 min/week) was associated with reduced risk of macrovascular events (HR = 0.80; 95%CI: 0.68–0.95), microvascular events (HR = 0.76; 95%CI: 0.63–0.92), and HF (HR = 0.65; 95%CI: 0.46–0.92). The minimum dose of MVPA for lowering the risk of composite events was approximately 59.0 min/week. More time spent in SB was associated with an increased risk of composite events (high vs. low, HR = 1.17; 95%CI: 1.02–1.35) and HF (high vs. low, HR = 1.54; 95%CI: 1.09–2.20). Replacement of 30 min of SB (HR = 0.73; 95%CI: 0.65–0.81) and LPA (HR = 0.74; 95%CI: 0.66–0.83) with MVPA dramatically reduced the risk of composite events. Conclusion: Adherence to a higher amount of accelerometer-measured PA, especially MVPA at least 59 min/week, is associated with reduced risks of macrovascular and microvascular events among individuals with T2DM and prediabetes. Replacement of SB and LPA with MVPA helped lower the risk of diabetic vascular events.